Invisible Storytellers : Voice-Over Narration in American Fiction Film - Kozloff, Sarah (Book collections on Project MUSE., 1989)
Let me tell you a story, each film seems to offer silently as its opening frames hit the screen. But sometimes the film finds a voicean off-screen narratorfor all or part of the story. From Wuthering Heights and Double Indemnity to Annie Hall and Platoon, voice-over narration has been an integral part of American movies. Through examples from films such as How Green Was My Valley, All About Eve, The Naked City, and Barry Lyndon, Sarah Kozloff examines and analyzes voice-over narration. She refutes the assumptions that words should only play a minimal role in film, that "showing" is.